2020
DOI: 10.18632/aging.103670
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-216a-3p promotes sorafenib sensitivity in hepatocellular carcinoma by downregulating MAPK14 expression

Abstract: We investigated MAPK14-dependent resistance to sorafenib in hepatocellular carcinoma (HCC). Bioinformatics analysis and dual luciferase reporter assays in HCC cell lines showed that miR-216a-3p directly binds to the 3’UTR of MAPK14 mRNA and downregulates MAPK14 protein expression. Consequently, miR-216a-3p expression correlates inversely with MAPK14 protein levels in HCC patient tissues. miR-216a-3p overexpression significantly increases the sorafenib sensitivity of HCC cells by suppressing MAPK14 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…ATF2 was shown to repress IFNβ1 transcription and to promote resistance to chemotherapy in melanoma [ 51 ]. Importantly, previous studies have found that ATF2 knockdown can increase the sensitivity of hepatocellular carcinoma cells to sorafenib [ [52] , [53] , [54] ], but the underlying mechanism has remained elusive. Consistently, our data revealed that ATF2 inhibition markedly promoted sorafenib-induced ferroptosis, which in turn enhanced the anticancer effects of sorafenib on GC cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…ATF2 was shown to repress IFNβ1 transcription and to promote resistance to chemotherapy in melanoma [ 51 ]. Importantly, previous studies have found that ATF2 knockdown can increase the sensitivity of hepatocellular carcinoma cells to sorafenib [ [52] , [53] , [54] ], but the underlying mechanism has remained elusive. Consistently, our data revealed that ATF2 inhibition markedly promoted sorafenib-induced ferroptosis, which in turn enhanced the anticancer effects of sorafenib on GC cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…They incompletely or completely bind to the 3' untranslated region (3'-UTR) of target mRNAs, thus regulating cell signaling pathways through negatively mediating post-transcriptional gene expression or degrading mRNAs (17,18). Studies have shown that miR-216a-3p promotes cancer (19)(20)(21), and many reports showed that miR-216a-3p significantly influenced the activity of Wnt/β-catenin signaling pathway. Song et al (22).…”
Section: Introductionmentioning
confidence: 99%
“…miR-631 targets PTPRE to dampen HCC migration, invasion, EMT, and intrahepatic metastasis [ 34 ]. Similar effects on liver cancer are also reflected in the other miRNAs like miR-199a-3p [ 35 ], miR-124-3p [ 36 ], and miR-216a-3p [ 37 ]. miR-373-3p is a novel miRNA first uncovered by Syring et al Its expression is substantially heightened in the serum of patients suffering from testicular germ cell tumors [ 38 ].…”
Section: Discussionmentioning
confidence: 83%